From musician to extirpator: Some notes on Francisco Otal in Lima and La Plata from 1613 to 1618 - Hidalgo Lehuedé, Jorge (2013)
This paper analyzes the early years of the priest Francisco Otal in the Archdiocese of Lima and La Plata. His ecclesiastical career, which led him to doctrinero in San Francisco de Chiuchiu to racionero of the Cathedral of La Plata, was preceded by a career as a musician and singer, helped by the interpretative strength og his record as tiple capon. It was this «officio of angels» which approached to Francisco de Otal to both the cathedral chapels of Lima and La Plata as to the prelates and members of church councils. As a consequence, his first appointment in Lima, in 1613, was very close and coincided with the early years of the process of extirpation of idolatry. Francisco Otal met its main protagonists, including the Archbishop Bartolomé Lobo Guerrero and other ecclesiastical authorities, deacons and field ground as Francisco de Avila that will surely preached this form of evangelization moving from persuasion to compulsion. Francisco de Avila met him agin in La Plata, in 1618, as well as speeches rejecting of idolatry which incorporated the first platense synod (1619-1690). Both experiences were the basis for its activity in Atacama rejecting and also allowed him to define new strategies for positioning himself within church networks of La Plata.